Maternal immune activation, central nervous system development and behavioral phenotypes. Issue 20 (14th November 2018) - Minakova, Elena; Warner, Barbara B.
Abstract : Maternal immune activation (MIA) refers to a maternal immune system triggered by infectious or infectious‐like stimuli. A cascade of cytokines and immunologic alterations are transmitted to the fetus, resulting in adverse phenotypes most notably in the central nervous system. Epidemiologic studies implicate maternal infections in a variety of neuropsychiatric disorders, most commonly autism spectrum disorders and schizophrenia. In animal models, MIA causes neurochemical and anatomic changes in the brain that correspond to those found in humans with the disorders. As our understanding of the interactions between environment, genetics, and immune system grows, the role of alternative, noninfectious risk factors, such as prenatal stress, obesity, and the gut microbiome also becomes clearer. This review considers how infectious and noninfectious etiologies activate the maternal immune system. Their impact on fetal programming and neuropsychiatric disorders in offspring is examined in the context of human and animal studies.